Pengaruh Pelatihan Kerja, Pengembangan Karir, dan Stres Kerja Terhadap Prestasi Kerja Pegawai di PT Industri Jamu dan Farmasi Sido Muncul Tbk - Erfianto, Indra Rasyid; Dwiarti, Rina (Peneliti.net, 2025)
Human resources that have good abilities and loyalty are important for the company. The company develops the abilities of employees and organizations to be able to compete and grow faster in the economy. This type of research uses quantitative research. In this study, the researcher uses primary data sources and secondary data. The results of the research that have been described in this study can be concluded as follows, starting from job training has a positive influence on employee work performance at PT Industri Jamu dan Farmasi Sido Muncul Tbk. Career development does not have a significant effect on employee work performance at PT Industri Jamu dan Farmasi Sido Muncul Tbk. Work stress does not have a significant effect on employee work performance at PT Industri Jamu dan Farmasi Sido Muncul Tbk.